2000
DOI: 10.1518/001872000779698097
|View full text |Cite
|
Sign up to set email alerts
|

Postural Instability and Motion Sickness in a Fixed-Base Flight Simulator

Abstract: We evaluated the prediction that postural instability would precede the subjective symptoms of motion sickness in a fixed-base flight simulator. Participants sat in a cockpit in a video projection dome and were exposed to optical flow that oscillated in the roll axis with exposure durations typical of flight simulation. The frequencies of oscillation were those that characterize spontaneous postural sway during stance. Head motion was measured prior to and during exposure to imposed optical flow. Of 14 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 18 publications
7
81
0
Order By: Relevance
“…This result resembles similar findings from studies of video games [8], virtual environments [6], and vehicle simulators [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result resembles similar findings from studies of video games [8], virtual environments [6], and vehicle simulators [7].…”
Section: Discussionsupporting
confidence: 88%
“…This effect has been observed in laboratory devices, virtual environments, flight simulators, and console video games [5][6][7][8]. Interestingly, in console video games postural instability and motion sickness are common among individuals who control the game (i.e., players), and occur in games that depict ambulation (i.e., walking or running) rather than vehicular travel [8].…”
Section: Introductionmentioning
confidence: 93%
“…However, in recent studies attempting to determine predictors of motion sickness, it has been found that motion sickness was preceded and predicted by gross disruptions in postural control. [48][49][50] In other words, instability in postural control seems to have led to physiological and behavioral dysfunction.…”
Section: Postural Control and Motion Sicknessmentioning
confidence: 99%
“…Stoffregen et al (1999a;1999b; instructed participants to fixate a distant target or a nearby target while standing. Reliable variations in parameters of postural sway were elicited by changes in the fixation task.…”
Section: Independent Specification?mentioning
confidence: 99%